The Effectiveness of Qualified Independent Supervisory Boards : Evidence from Indonesia - Joni, Joni; Natalia, Maria; En, Tan Kwang; Pranata, Ilham; Hasianna, Winda Riama (Universitas Pendidikan Indonesia, 2021)
The objective of our empirical research is to examine the characteristics of independent supervisory board (SB) on corporate’s risk in dual tier corporate board setting, Indonesia from 2015-2017. This study is different with previous literature in several ways. First, we examine the value of qualified independent SBs in Indonesian dual board setting, while previous studies focus on one-tier board system and developed countries. Second, we also test the effectiveness of several characteristics of qualified independent supervisory board, including size, financial expertise, and tenure on operating and market risks. Based on 1,089 firm-year observations, the results suggest that both independent SB size and financial expertise help company to reduce operating and market risks. Further, we find that independent SB tenure is negatively associated with operating risk. Our results are robust after addressing endogeneity problem.